2013
DOI: 10.1007/s00134-013-3033-6
|View full text |Cite
|
Sign up to set email alerts
|

Triage of intensive care patients: identifying agreement and controversy

Abstract: Rationale Intensive care unit (ICU) resources are limited in many hospitals. Patients with little likelihood of surviving are often admitted to ICUs. Others who might benefit from ICU are not admitted. Objective To provide an updated consensus statement on the principles and recommendations for the triage of patients for ICU beds. Design The previous Society of Critical Care Medicine (SCCM) consensus statement was used to develop drafts of general and specific principles and recommendations. Investigators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 31 publications
1
77
0
12
Order By: Relevance
“…Several studies have confirmed the very poor long-term prognosis of elderly patients admitted to the ICU [2][3][4][5][6][7][8][9] (Table 1). Importantly, factors such as an atypical presentation with delayed diagnosis and treatment, suboptimal management (because guidelines are not tailored for an elderly population), lower physiologic reserve, immuno-senescence coupled with an inadequate immune response, more frequent and earlier treatment limitations, and finally inadequate discharge policies (location, timing) may account for or at least contribute to excess mortality.…”
Section: Available Evidencementioning
confidence: 83%
“…Several studies have confirmed the very poor long-term prognosis of elderly patients admitted to the ICU [2][3][4][5][6][7][8][9] (Table 1). Importantly, factors such as an atypical presentation with delayed diagnosis and treatment, suboptimal management (because guidelines are not tailored for an elderly population), lower physiologic reserve, immuno-senescence coupled with an inadequate immune response, more frequent and earlier treatment limitations, and finally inadequate discharge policies (location, timing) may account for or at least contribute to excess mortality.…”
Section: Available Evidencementioning
confidence: 83%
“…Similarly, when a panel of international experts in intensive care medicine issued a list of criteria that could assist the decision making processes regarding admission or refusal of admission of patients to ICU there was a strong consensus that age should not be considered as a sole decision making criterion [1]. Nevertheless, economic pressures, the need for rationing of ICU beds [2] and changing demographics -in particular the aging of most populationsmight jeopardize this idealized view of ICU access and treatment for elderly patients [3].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Last, Sprung and the Eldicus investigators, consultants, and experts provided an updated consensus statement on the triage of patients for ICU beds. They reached a consensus for most general and specific ICU triage principles and recommendations [69].…”
Section: Incidence Of Potential Missed Organ Donors In the Icu And Emmentioning
confidence: 99%